2015
DOI: 10.5433/1679-0359.2015v36n2p1135
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative parameters of sugarcane silages treated with urea and calcium oxide

Abstract: The objective was to evaluate the fermentation parameters, chemical composition and fractionation of carbohydrates of sugarcane silages treated with urea and calcium oxide (CaO). Upon ensiling, the treatments applied to the sugarcane were: 1% urea; 0.5% urea + 0.5% CaO; and 1% CaO, in relation to a control silage, without additive. The chemical additives (urea and CaO) were added at ensiling, in an amount calculated based on the fresh matter (as is). A completely randomized design consisting of four treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
7
1
1
Order By: Relevance
“…() and Martins et al. () investigated and described the use of urea and calcium oxide as alkalinizing chemical additives in the ensiling of sugarcane. According to them, these additives have the potential to improve the nutritional value of the forage, reducing its fibre content and increasing its digestibility, because addition of alkaline agents is related to the action of alkaline hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…() and Martins et al. () investigated and described the use of urea and calcium oxide as alkalinizing chemical additives in the ensiling of sugarcane. According to them, these additives have the potential to improve the nutritional value of the forage, reducing its fibre content and increasing its digestibility, because addition of alkaline agents is related to the action of alkaline hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of urea in the ammoniation of pearl millet did not lead to a reduction of the fibrous fraction of the silages, as observed in other scientific studies (Keskin et al, 2005;Rong et al, 2013). Martins et al (2015) also found an increase in ADF and lignin contents in sugarcane silages treated with urea. These authors attributed this effect to the nonsolubilization of these cell wall components.…”
Section: Resultsmentioning
confidence: 67%
“…Urea did not prevent losses of these nutrients. Martins et al (2015) also observed a lower NFC content in sugarcane silage with 1% urea, and suggest that Table 3. Chemical composition and fermentation profile of pearl millet silages, at 600 kgm -3 compaction density, treated with urea levels at two evaluation times -opening (0 hour) and exposure to air (72 hours).…”
Section: Resultsmentioning
confidence: 67%
“…Furthermore, chemical treatment with calcium oxide (CaO) may improve the nutritional value of forage by reducing fiber content and increasing digestibility as the addition of alkaline additives is related to the action of alkaline hydrolysis (Romão et al, 2013;Chizzotti et al, 2015;Martins et al, 2015). In this context, feeding cattle in feedlots with freshly cut or ensiled sugar cane may be feasible, especially in sugar cane producing regions.…”
Section: Introductionmentioning
confidence: 97%